Effectiveness of a low-cost body weight support training device in the rehabilitation of cerebral palsy. (November 2016) - Sharan, Deepak; Rajkumar, Joshua Samuel; Balakrishnan, Rajarajeshwari; Kulkarni, Amruta; Selvakumar, Kalpana; Gampa, Sivakrishna; Mohandoss, Mathankumar; Ranganathan, Rameshkumar
Background: Body weight supported treadmill training (BWSTT) has been proven to be effective in rehabilitation of persons with cerebral palsy (CP). However, it has still not found widespread usage, especially in industrially developing countries, due to its high cost. Treadmill training promotes a rhythmical movement of the lower extremities through motor learning, which can be enhanced by BWSTT for persons with CP. Hence, the research and development team of a tertiary level neuromusculoskeletal rehabilitation center designed a low-cost body weight support training (BWST) device. The aim of this study was to evaluate the effectiveness of the BWST device on gait and ambulation in persons with CP post single-event multilevel surgery (SEMLS) of the lower extremities. Method: A randomized controlled trial was conducted in 50 persons with CP aged between 5 and 20 years, who underwent a type of SEMLS called single-event multilevel lever arm restoration and anti-spasticity surgery (SEMLARASS). They were randomly assigned to two groups: group A ( n  = 25) received gait training and treadmill training with the BWST device, and group B ( n  = 25) received gait training and treadmill training without the BWST device. The designed BWST device was manually operated and based on an un-weighing principle in which a vest of different sizes un-weighed 10–30% of the individual's weight transmitted to the ground by means of adjustable counterweights fixed on a movable metallic frame which had an adjustable top lever (holding the vest) and a handle bar for the patient to hold. The entire cost for the finished BWST device was estimated around 700 USD. The study duration was 5 weeks with 1 h of intervention per day for 6 days per week. Physician Rating Scale (PRS), Dynamic Gait Index (DGI) and Functional Mobility Scale (FMS) were the primary outcome measures. Results: Group A showed significant positive differences in the scores of PRS ( p  < 0.001), DGI ( p  < 0.001) and FMS ( p  < 0.01) when compared with group B, 5 weeks after the intervention, and the results were maintained at a follow-up of 12 months. Conclusion: The low-cost BWST device was found to be clinically effective in improving gait and ambulation in persons with CP following SEMLARASS.